2007
DOI: 10.1007/s10646-006-0122-0
|View full text |Cite
|
Sign up to set email alerts
|

Mysid crustaceans as standard models for the screening and testing of endocrine-disrupting chemicals

Abstract: Investigative efforts into the potential endocrine-disrupting effects of chemicals have mainly concentrated on vertebrates, with significantly less attention paid to understanding potential endocrine disruption in the invertebrates. Given that invertebrates account for at least 95% of all known animal species and are critical to ecosystem structure and function, it remains essential to close this gap in knowledge and research. The lack of progress regarding endocrine disruption in invertebrates is still largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 131 publications
(151 reference statements)
0
29
0
1
Order By: Relevance
“…Finally, in the amphipod Melita plumulosa, Chung et al [15] have recently shown that a significant difference in two life-history traits (female length and fertility) could be observed between organisms from polluted and unpolluted waterways. To date, no specific ED biomolecular markers are available in the crustaceans currently used in aquatic ecotoxicology [17,[33][34][35]. This can be attributed for the most part to the shortage of fundamental knowledge of their endocrine systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in the amphipod Melita plumulosa, Chung et al [15] have recently shown that a significant difference in two life-history traits (female length and fertility) could be observed between organisms from polluted and unpolluted waterways. To date, no specific ED biomolecular markers are available in the crustaceans currently used in aquatic ecotoxicology [17,[33][34][35]. This can be attributed for the most part to the shortage of fundamental knowledge of their endocrine systems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, given the phylogenetic distance between species and the molecular divergence through bilaterian animal evolution, ED biomarkers available in aquatic vertebrates cannot be easily and/or should not directly be applied to the majority of invertebrates, because these two groups belong to two distinct ancient lineages of animals (deuterostomes vs protostomes). Consequently, as recommended by Verslycke et al [34], bioassays should be developed to measure the impact of physicochemical stressors on various physiological process under endocrine regulation, such as growth, molting, embryonic development, vitellogenesis, and fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Americamysis bahia (formerly Mysidopsis bahia) is commonly used as a test organism in ecotoxicology (reviewed in Verslycke et al 2007), so substantial effort has been devoted to the standardization of laboratory culturing methods and production of uniformly conditioned individuals (Lussier et al 1988. Individuals are 5 to 10 mm in length (rostrum to telson).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Estuarine regions are known to be often subjected to intensive discharges of aquaculture effluent water from aquaculture ponds and they are also the sites for aquaculture cage culture. In addition, there has been an increasing interest in using the brackish water mysis as model species for environmental toxicological test Verslycke et al 2007). …”
Section: Introductionmentioning
confidence: 99%